The Role of Public Relations of the Kurdistan Regional Government in Attracting Investors - HamaSaleh, Sangar K.; Ali, Hoshiar M. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract: This paper entitled (The Role of Public Relations of the Kurdistan Regional Government in Attracting Investors) is an attempt to answer the following questions: How does public relations the main tool and its management in its mission, objectives, and models attract investors to the Kurdistan Regional Government. What is the role of public relations for the KRG in attracting investors to the region. The research followed the descriptive statistical approach for the purpose of data collection, analysis, interpretation and search for the phenomenon. An applied research tool matches the methodology, goal, purpose and nature of the research community. A questionnaire and data analysis through the (SPSS) program was used to analyse demographic elements and aspects. The research population is the public relations department of the Kurdistan Regional Government, the public relations commissions of the Kurdistan Regional Government, and all ministries that include public relations. More specifically, this includes the Public Relations Department, 10 of the 19 ministries in the 9th Cabinet, and the KRG’s Department of Foreign Relations. The research targeted this population census, as there are only these ministries and one department of relations have offices in the structure of ministries and departments. The research sample included 96 employees from the Department of Relations of both sexes. The objectives of this paper are as follows, Disclosure of the role of public relations for the Kurdistan Regional Government in attracting investors to the Kurdistan Region. Here are the main findings of this study; there is a direct and valuable relationship between the KRG’s public relations and the attraction of investors to the region. Public relations have a valuable statistical impact on attracting investors to the Kurdistan Regional Government., The success of the KRG public relations in the ministry and the investment committee is due to a collective strategy to attract Kurdish investors within the region, from Europe, Iraqi investors, and investors from home and abroad to the KRG. The Department of Public Relations in the ministries of the Kurdistan Regional Government and investment committees employ a successful plan in dealing with investors at home and abroad in order to create an economic framework for appealing interest and benefiting from it within the Kurdistan Region.